Prospective study revealed prognostic significance of responses in leptomeningeal metastasis and clinical value of cerebrospinal fluid-based liquid biopsy. (November 2018) - Xu, Yan; Hu, Min; Zhang, Meizhuo; Zhong, Wei; Yin, Xiaolu; Sun, Yun; Chen, Minjiang; Zhao, Jing; Si, Xiaoyan; Wang, Hanping; Zhang, Xiaotong; Zhang, Li; et al.
Highlights: 93.9% of the NSCLC-LM patient cohort carried oncogenic driver mutations. The composite endpoint for objective response evaluation of LM was valid. EGFR mutation testing by CSF showed high concordance with primary tumor. EGFR T790 M occurrence in CSF was relatively rare at diagnosis of LM. Abstract: Objective: Leptomeningeal metastasis (LM) secondary to non-small cell lung cancer (NSCLC) is a devastating complication associated with poor prognosis. Diagnosis and assessment of responses in LM have been challenging due to limitation of traditional imaging tools and lack of standard evaluation criteria until very recently. To bridge this gap, we conducted the first prospective, observational study in cytologically diagnosed NSCLC-LM patients (NCT02803619). Patients and methods: A total of 49 NSCLC-LM patients were enrolled. LM responses were evaluated with a composite endpoint integrating neurological symptoms, cerebrospinal fluid (CSF) parameters and central nervous system (CNS) imaging. Primary outcome was overall survival (OS) after diagnosis of LM. Exploratory endpoint was the association between OS and prognostic factors. Primary tumor and CSF samples were collected for biomarker analysis. Results: 93.9% of the cohort carried oncogenic drivers, and 85.7% harbored EGFR activating mutations. Median OS since LM diagnosis of the overall population was 9.7 months. EGFR mutant LM patients had a longer survival compared with wildtype ones. LM clinical responses assessed by the composite endpoint showed significant correlation with OS. Status of EGFR activating mutations was highly concordant between primary tumor and CSF. T790 M occurrence in CNS lesions was relatively rare and associated with intracranial exposure level of EGFR-TKIs. Conclusion: Our results supported the composite endpoint for objective response evaluation of LM was valid, suggested LM outweighed peripheral lesions on the impact to patient survival, and emphasized the urge and promise of development of CNS-penetrant targeted therapies to improve clinical outcome of NSCLC-LM patients.